The Antifungal and nematicidal potentials of vernonia amygdalina on cowpea (vigna unguiculata (l.) walp) (2013)
Vernonia amygdalina is a herbaceous plant that grows in the wild and is widely cultivated as food crop in sub-Saharan Africa. The study evaluated its fungicidal and nematicidal Potentials. Isolates of Macrophomina phaseolina were obtained from germinating cowpea variety IT845-2246-4 growing on natural infested soil at screen house in International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria (70 261 N, 50 541 E) and then subcultured to achieve pure culture, while inculum of the root knot nematode, Meloidogyne sp. was obtained from infested Celosia sp. plants through Standard pathological and hematological procedures. Aqueous and ethanol extracts of V. amygdalina at various concentrations of 2.5%, 5% and 10% were prepared and tested in-vitro against Macrophomina phaseolina and the root knot nematode Meloidogyne sp. At incubation of 27.50C-30C for 7-days, radial growth of the plated M. phaseolina was measured at 24-hour intervals and percentage fungitoxicity calculated, while Meloidogyne sp. egg hatch and Td juvenile stage mortality were observed at 24-hour intervals for a 10- day period. Fungitoxicity tests showed aqueous extracts of 5% and 10% concentration significant/y inhibited mycelia growth (32.08% and 34.77%, respectively) when compared with the control Ethanol extracts exhibited 100% fungicidal activity. Furthermore, egg hatch by Meloidogyne sp. was completely inhibited by both extracts preparation at 2.5% and 5% concentrations while 100% mortality of Meloidogyne sp. juveniles was observed on the fifth day post-treatment. Vernonia amygdalina was identified as a natural, readily available and cheap source of fungicide and nematicide. It is recommended for control of charcoal rot infection and Meloidogyne sp. infestation of cowpea.